The long‐term health risks of ART : Epidemiological data and research on animals indicate that in vitro fertilization might create health problems later in life - Hunter, Philip (EMBO Rep, 2017)
Since the birth of Louise Brown 39 years ago, scientists have been suspecting that assisted reproductive technologies could create long‐term health risks. While evidence remains inconclusive, ongoing research and improvements help to reduce such risks. [Image: see text]